Ekspresi Eufemisme dan Disfemisme dalam Artikel Berita Sekretariat Kabinet Indonesia dan Terjemahannya - Muliawati, Ni Wayan Pering (Jurnal Penerjemahan, 2022)
Euphemism and dysphemism are frequently used in news text, since they are believed to be able to attract the readers. These kinds of expressions are also commonly found in Indonesian Secretariat Cabinet (Setkab) online news. The research aims to find out how euphemistic and dysphemistic expressions are translated from Indonesian to English in the news. The methodology used on the research is descriptive qualitative, through mapping and analyzing 20 news texts and their translations. The researcher used Technique of Translation theory that was proposed by Molina and Albir (2002) to analyze the translation techniques applied in the translations. There are thirty-four expressions containing euphemism and dysphemism in thexts analysed, most ofwhich are dysphemized and modulated in the target texts. The ways the two figures of speech are translated in the target texts, however, do not reflect the particular purposes commonly associated with them, namely toadd or neutralize connotations. Rather, they mainly serve to add variations to the texts. Keywords: euphemism, dysphemism, technique of translation,news, text